Self-Managing osteoporosis treatment for well-being recovery mediated by the (in)visibility of the disease signs - de Souza, Luciana Bronzi; da Silva Mazeto, Gláucia Maria Ferreira [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (FapUNIFESP (SciELO), 2010)
The present study aimed to understand patients' experience with osteoporosis treatment. The methodological and theoretical frameworks were, respectively, the Grounded Theory and Symbolic Interactionism. The research subjects were 12 patients monitored in a specialized outpatient unit. The obtained statements were transcribed and analyzed, leading to a synthesis of the described themes. From the analysis process, two phenomena emerged: self-evaluating health conditions according to the disease signs and making a decision about the treatment targeting at well-being. The realignment and the inter-relationship of the components belonging to these phenomena (themes, categories, and subcategories) allowed to identify the core category: self-managing osteoporosis treatment for well-being recovery mediated by the (in)visibility of the disease signs. Furthermore, it allowed for the design of a theoretical model concerning the process used by the player in his cyclic movement of the experience, between adherence to and relaxation from the osteoporosis treatment.
Autogerindo o tratamento da osteoporose no regaste do bem-estar, mediado pela (in)visibilidade de indicadores da doença
Keywords: Chronic disease; Osteoporosis; Patient compliance; Qualitative research; Treatment outcome